2019
DOI: 10.1038/s41598-018-38408-3
|View full text |Cite
|
Sign up to set email alerts
|

IL1RL1 is dynamically expressed on Cbfb-MYH11+ leukemia stem cells and promotes cell survival

Abstract: Acute myeloid leukemia (AML) is often characterized by the presence of specific, recurrent chromosomal abnormalities. One of the most common aberrations, inversion of chromosome 16 [inv(16)], generates the fusion oncogene CBFB-MYH11. Previously, we used a mouse knock-in model to show that Cbfb-MYH11 induces changes in gene expression and results in the accumulation of abnormal myeloid cells, a subset of which are enriched for leukemia stem cell (LSC) activity. One gene upregulated by Cbfb-MYH11 encodes the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
(49 reference statements)
4
13
0
Order By: Relevance
“…Interestingly, we found that there was a statistically signi cant decrease in cells in G0/G1 phase in IL-33-treated cells, as compared to the untreated cells (Fig.4E). These results are consistent with our earlier work showing that IL-33 inhibits apoptosis via activating p38 MAPK and upregulates the percentage of cells in S phase in primary mouse leukemia cells and human AML cell line [16,18]. Together, our data indicate that IL-33 promotes cell survival by stimulating p38 MAPK pathway in AML patient samples.…”
Section: Il-33 Promotes Cell Survival Via P38 Mapk Pathway In Primarysupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, we found that there was a statistically signi cant decrease in cells in G0/G1 phase in IL-33-treated cells, as compared to the untreated cells (Fig.4E). These results are consistent with our earlier work showing that IL-33 inhibits apoptosis via activating p38 MAPK and upregulates the percentage of cells in S phase in primary mouse leukemia cells and human AML cell line [16,18]. Together, our data indicate that IL-33 promotes cell survival by stimulating p38 MAPK pathway in AML patient samples.…”
Section: Il-33 Promotes Cell Survival Via P38 Mapk Pathway In Primarysupporting
confidence: 93%
“…Previously, we found that IL1RL1 is highly expressed in leukemia cells expressing CBFB-MYH11 [16,17]. Further, we demonstrated that exogenous IL-33 treatment inhibited apoptosis of primary mouse leukemia cells as well as human AML cell line, HL-60 [18].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…We must also consider that the IL-33/ST2 system in the BM can be stimulated both in hematopoietic cells and in stromal/nonhematopoietic cells. Activation of ST2 on these cells provokes the production of several cytokines (IL-6, GM-CSF, G-CSF, and IL-3) that can activate the STAT5 pathway and can cause resistance to imatinib mesylate [68,82].…”
Section: Il-33 and Hematologic Malignanciesmentioning
confidence: 99%
“…Employing Cbfb-MYH11 knock-in mice, it was reported that ST2 is present on cells with high leukemia stem cell activity. Moreover, ST2 + cells can survive chemotherapy better than ST2 − cells in vivo [82]. Levescot et al made a similar observation for BCR-ABL1 in CML [77].…”
Section: Il-33 and Hematologic Malignanciesmentioning
confidence: 99%